Neutralising effects of small molecule toxin inhibitors on nanofractionated coagulopathic Crotalinae snake venoms - Chunfang Xie; Julien Slagboom; Laura-Oana Albulescu; Govert W. Somsen; Freek J. Vonk; Nicholas R. Casewell; Jeroen Kool (Elsevier, 2020)
Repurposing small molecule drugs and drug candidates is considered as a promising approach to revolutionise the treatment of snakebite envenoming. In this study, we investigated the inhibiting effects of the small molecules varespladib (nonspecific phospholipase A2 inhibitor), marimastat (broad spectrum matrix metalloprotease inhibitor) and dimercaprol (metal ion chelator) against coagulopathic toxins found in Crotalinae (pit vipers) snake venoms. Venoms from Bothrops asper, Bothrops jararaca, Calloselasma rhodostoma and Deinagkistrodon acutus were separated by liquid chromatography, followed by nanofractionation and mass spectrometry identification undertaken in parallel. Nanofractions of the venom toxins were then subjected to a high-throughput coagulation assay in the presence of different concentrations of the small molecules under study. Anticoagulant venom toxins were mostly identified as phospholipases A2, while procoagulant venom activities were mainly associated with snake venom metalloproteinases and snake venom serine proteases. Varespladib was found to effectively inhibit most anticoagulant venom effects, and also showed some inhibition against procoagulant toxins. Contrastingly, marimastat and dimercaprol were both effective inhibitors of procoagulant venom activities but showed little inhibitory capability against anticoagulant toxins. The information obtained from this study aids our understanding of the mechanisms of action of toxin inhibitor drug candidates, and highlights their potential as future snakebite treatments.